PENGOLAHAN AIR LIMBAH RUMAH TANGGA SECARA BIOLOGIS DENGAN MEDIA LUMPUR AKTIF Suatu Usaha Pemanfaatan Kembali Air Limbah Rumah Tangga Untuk Kebutuhan Mandi Dan Cuci - Deissy L Nusanthary; Elliza Rosida Colby; Herry Santosa (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Liquid wastes water, the former can be processed into water that can be used again in accordance with needed. Research carried out using a biologically active sludge media. The experiment is done through two stages (1) the characterization of waste water (2) wastewater treatment. Characterization of wastewater is meant to find out the characteristics of the waste water based on pH and clarity level. Stages of wastewater treatment is performed in four aerator box, each with comparative weight of active sludge per unit volume (MLSS 1000, 2000, 3000 MLSS MLSS and MLSS 4000 mg/litre). On each end of the experiment conducted test pured, pH, water softening, and surfactants of kehari for seven days. From the results of the experiment retrieved data (1) the waste Water need further processing to put back as water bath and laundry (2) Review of test parameters pH, clarity, and water softening. processing for 6 days will provide product water processed relatively better on the use of MLSS 1000mg/l (3) of the day to day, during the process of decreasing the levels of processing takes place even though it has not yet reached the levels of surfactants are surfactants are equal to zero, according to SK menkes RI in 2002.